Preconditions for the establishment of forest steppe non-native floras of the protected areas of Ukraine (CHORNOMORSKI BOTANICAL JOURNAL, 2014)
Non-native floras of 13 protected areas, located within the range between 51˚43′09″ – 48˚23′57″ N and 26˚10′00″ – 37˚47′00″ E have been studied. These floras represent the plant diversity of the Ukrainian Forest Steppe. Preconditions for the establishment of alien floras comprised a number of abiotic and biotic factors of the recipient ecosystem. At the level of a protected area, the preconditions included location in terms of natural zoning, total area, land-use structure, river banks, transport routes, and period of time under protection. At the level of a single flora, the main preconditions were total number of species, share of alien species, and possible threats of invasions from the surrounding areas. A taxonomic list included 364 alien species, 90 (25 %) of which were casuals. The number of alien species in the studied floras ranged from 52 to 229, while the total number of species varied from 418 to 1138. The share of non-natives ranged from 9 to 28 %, with the average of 16 %. However, after casual alien species had been excluded, it was 8 –26 %, with the average of 14 %. The number of non-natives was increasing as the number of indigenous species and the total number species were increasing too. The resident floristic and habitat diversity within the studied areas didn’t seem to be a barrier for penetration and naturalization of alien species. However, a weak inverse correlation between the proportion of non-natives and native species numbers allowed us to assume that the number of native species, corresponding to the "complete flora", served as a penetration barrier for exotic species.
Keywords: non-native flora, alien plant species, nature reserve fund, Forest Steppe, Ukraine.